Analysis on Defocusing and Astigmatism of Electron Beam Selective Melting Machines. (October 2020) - Sun, Botong; Yin, Bohua; Wang, Pengfei; Xu, Guanglu; Liu, Junbiao; Han, Li
Abstract: Affected by defocusing and astigmatism, the quality of electron beam steadily deteriorated with increasing deflection distance, limiting the processing area of SEBM machines. The relationship among beam spot size, deflection distance and deflection direction are studied by numerical simulation, which explains the cause of decreasing power density. The experimental results show that defocus is the main factor affecting the beam spot size when the deflection distance is less than 100 mm and astigmatism is the main factor at a larger deflection distance. Then, the chessboard electron imaging experiment is carried out to verify that the spot size increases with the deflection distance. Thus, dynamic focusing and astigmatism should be introduced at the same time to minimize beam area.